The role of social projects in reducing unemployment in the Republic of Kazakhstan (Вестник КазНУ. Серия Экономическая, 2016)
To date, the concept of "project" and "social project" are widely used in discussions on social and economic development of the country as a whole. The project is coordinated execution of multiple, inter-related activities, and, thirdly slowness limited in time, with a defined beginning and end. Socially project - is designed by the proponent of social innovation, which aims to create, upgrade or maintenance of the changing environment of the material or spiritual values, which is the space - time and resource boundaries and whose impact on people deemed positive in their social value. Thus, the project of social work as a system formulated project objectives established for the purpose of social institutions, physical objects, social protection systems, developed and approved by the relevant dokumentov- programs, plans, calculations, estimates, calculation of the necessary resources (material, financial, labor, time), the complex management decisions, activities to achieve their goals.